2009
DOI: 10.1093/molbev/msp186
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin Suggests a Close Relationship of Remipedia and Hexapoda

Abstract: The Remipedia are enigmatic crustaceans from anchialine cave systems, first described only 30 years ago, whose phylogenetic affinities are as yet unresolved. Here we report the sequence of hemocyanin from Speleonectes tulumensis Yager, 1987 (Remipedia, Speleonectidae). This is the first proof of the presence of this type of respiratory protein in a crustacean taxon other than Malacostraca. Speleonectes tulumensis hemocyanin consists of multiple distinct (at least three) subunits (StuHc1-3; Hc, hemocyanin). Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…The latter result (crustacean paraphyly) arises from the use of methodologies that are more philosophically sound, that is, implied character weights rather than equal weights (see Methods for justification of implied weights), and more comprehensive taxon sampling, that is, including extinct and extant taxa rather than extant alone. When myriapods were removed from these data sets, the remipedes (plus the Silurian fossil Tanazios 28 in the total data set) resolved as the closest extant sister taxon to hexapods (and euthycarcinoids), thus retrieving crustacean paraphyly and mirroring the molecular support for a remipede sister group to hexapods 1,2,29 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The latter result (crustacean paraphyly) arises from the use of methodologies that are more philosophically sound, that is, implied character weights rather than equal weights (see Methods for justification of implied weights), and more comprehensive taxon sampling, that is, including extinct and extant taxa rather than extant alone. When myriapods were removed from these data sets, the remipedes (plus the Silurian fossil Tanazios 28 in the total data set) resolved as the closest extant sister taxon to hexapods (and euthycarcinoids), thus retrieving crustacean paraphyly and mirroring the molecular support for a remipede sister group to hexapods 1,2,29 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent molecular studies have strongly suggested that either Remipedia or Remipedia + Cephalocarida is most closely related to Hexapoda [11,45-47]. Therefore, the inclusion of samples from Remipedia and Cephalocarida in our future analyses is highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular and morphological studies have placed crustaceans along with hexapods into a pancrustacean clade (Figure 1A), revealing that crustaceans are paraphyletic (Mallatt et al, 2004; Cook et al, 2005; Regier et al, 2005; Ertas et al, 2009; Richter, 2002). Previously, the only available fully sequenced crustacean genome was that of the water flea Daphnia which is a member of the Branchiopoda (Colbourne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%